(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In this article, digital banking technologies, their composition, and directions for their effective use in the activities of commercial banks are widely covered. The scientific views of foreign and domestic scientists on banking technologies are deeply studied, analyzed and author’s opinions are expressed. Also, the banking technologies used in the world’s banks today are presented and their specific features and advantages are revealed. In addition, scientifically based suggestions on the effective use of banking technologies have been developed.